Association between Hospital Accreditation and Patient Satisfaction: A Survey in the Western Province of Iran - Mohebbifar, Rafat; Rafiei, Sima; Mohammadpoor Asl, Asghar; Ranjbar, Mohammad; Khodayvandi, Mona (Bangladesh Journal of Medical Science, 2017)
Background: In recent years accreditation programs have been developed to assess the quality of care and patient safety in hospitals. Quality is a multidimensional concept with patient satisfaction as one of the important facets. This study aimed to test any relationship between patient satisfaction and hospital accreditation. Material and Methods: A cross-sectional study of seven hospitals in Hamadan, Iran, was conducted in 2013. Patient satisfaction was analyzed through a self-made questionnaire and data on hospitals accreditation scores were obtained from the Curative Deputy of Hamadan University of Medical Sciences. Statistical analysis was done using SPSS 20. Results: Our research found out a strong relation between satisfaction scores and length of stay, hospital type, human resources condition, information, communication and education, medical equipment and physical structure, accessibility to clinical services, emotional support, management and coordination of care. Findings also revealed a significant negative association between hospital accreditation and patient satisfaction except for the domain of emotional support. Conclusion: Findings support healthcare managers with helpful information about the variables that are related to patient satisfaction. This understanding will make them capable to meet needs and preferences of patients more effectively. Study also confirmed the importance of developing an accreditation system based on outcome parameters and providing responsive services to patients which can positively impact their satisfaction. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.77-84